GRA24-Based DNA Vaccine Prolongs Survival in Mice Challenged With a Virulent Toxoplasma gondii Strain - Zheng, Bin; Lou, Di; Ding, Jianzu; Zhuo, Xunhui; Ding, Haojie; Kong, Qingming; Lu, Shaohong (Frontiers in Immunology, 2019)
Toxoplasma gondii causes zoonotic infections in a wide range of intermediate hosts and remains a threatening disease worldwide because of the lack of effective drugs and vaccines. Dense granule protein 24 (GRA24) is a novel essential virulence factor that is transferred into the nucleus of host cells from the parasitophorous vacuole to regulate gene expression. In the present study, bioinformatic analysis showed that GRA24 had a high score for B-cell and T-cell epitopes compared with surface antigen 1 (SAG1), which has been studied as a promising vaccine candidate. As a DNA vaccine, pVAX1-GRA24 was injected it intramuscularly into BALB/c mice and the induced immune response was evaluated. pVAX1-GRA24 induced high levels of a mixed Th1/ Th2 cytokines at 6 weeks after immunization. Antibody determinations, cytokines (interferon gamma (IFN-γ), interleukin (IL)-12, IL-4, IL-10), antigen-specific lymphocyte proliferation, CD4+ and CD8+ T lymphocytes, and cytotoxic T lymphocyte activity showed that mice immunized with pVAX1-GRA24 produced specific humoral and cellular immune responses. Activation of the interferon regulatory factor 8 (IRF8), nuclear factor kappa B (NF-κB), and T-Box 21 (T-bet) pathways was analyzed in the host immune response. Survival times were prolonged significantly (24.6 ± 5.5 days) in the mice immunized with pVAX1-GRA24 compared with the mice in the control groups, which died within 7 days of T. gondii challenge (p < 0.05). The results of the present study showed that pVAX1-GRA24 induced a T. gondii-specific immune response and thus represents a promising candidate vaccine to treat toxoplasmosis.